Estudio de factibilidad para la implementación de una empresa agroturística anexa al plantel avícola San Alfonso ubicada en la parroquia rural Moromoro del cantón Piñas provincia de El Oro - Peña Bernal, Alfonso Aurelio (2024)
The project seeks to provide authentic and sustainable tourism experiences that highlight the cultural and natural wealth of the region. The objective of the work is to determine the feasibility for the implementation of an agrotourism enterprise attached to the San Alfonso poultry plant in Moromoro, Piñas. Throughout the methodological process the place where the research was conducted was identified, it was determined that the approach is quantitative, deductive, exploratory, descriptive, explanatory and with a non-experimental design. The study population is economically active between 18 and 65 years old, giving a total of 11722 inhabitants. The sample was calculated resulting in 387 surveys. The results and analysis showed that the effective population for the first year is 6570 clients, from the balance between demand and supply it was determined that the unsatisfied demand for the first year is 2670 possible clients, the installed and used capacity for the first year amounts to 2600 users, the size of the investment is $ 6053, 5 which was financed 30% with equity and 70% with external capital, the cost of the service will have a value of $10 the project will generate income of $26000 for the first year. From the financial evaluation the NPV gave a positive result of $10561.10, the IRR gave a result of 72.36% higher than the opportunity cost, the Benefit Cost Ratio gave a result of 1.26, the capital recovery will be 1 year 5 months and 10 days. The sensitivity analysis supports an increase in costs of 11.5% and a decrease in income of 9% with these data it is concluded that the project is feasible. Key words: Project, investment, enterprise, agrotourism